Optimalisasi Keuntungan dalam Produksi Dengan Menggunakan Linear Programming Metode Simpleks: Studi Kasus Home Industry Jillys Kitchen di Pondok Pucung - Arifai, Mukhamad Khotib (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
Jillys Kitchen is a home industry in the culinary field that provides several types of snacks with various sizes and prices. In her business Jillys Kitchen encountered problems in combining available resources appropriately to obtain optimal profits by producing goods in optimal quantities. This study uses the simplex method to solve linear programming problems whose determination technique uses the optimal solution by counting many times or iterations that are carried out repeatedly with the help of POM QM Software for Windows V5. The purpose of this research is to optimize the production of snacks in the Jillys Kitchen home industry. This research method uses descriptive analysis method with a quantitative approach, describes and interprets the application of linear programming and obtains observable data results. The subject of this research is the production of Jillys Kitchen snacks with maximum profit. In this study there are 6 decision variables and 4 constraints. The decision variables used were regular size stick noodles (R), large size stick noodles (L), regular size macaroni (R), large size macaroni (L), regular size dumpling chips (R), and chips. dumplings with a large size (L). Constraints in this research are production materials (from noodle sticks, macaroni, and dumpling chips) and production capital. The result of this research is the optimal number of snacks to be produced by Jillys Kitchen. The results obtained are 10 large size noodle sticks (L), 60 large macaroni (L) and 63 large size dumpling chips (L) with a maximum profit of Rp.303.900.000/period.